The Existence of Fraction Domino Learning Media on the Mathematical Communication Skills of Elementary School Students - 'Arif, Muhammad; Wandini, Rora Rizky (Journal of Social Work and Science Education, 2025)
The purpose of this study was to examine the effect of fractional domino learning media on the mathematical communication skills of second-grade elementary school students. This study employed a quantitative approach with a quasi-experimental design, specifically a nonequivalent control group design. The experimental group received the treatment, while the control group did not. The sample consisted of 58 second-grade students from MIN 4 Kota. Two data collection techniques were used in this study: observation and a mathematical communication ability test. Data analysis was conducted using descriptive statistics, followed by normality and homogeneity tests, and hypothesis testing using independent sample t-tests. The results indicated that fractional domino learning media positively affected students’ mathematical communication abilities, as evidenced by the average post-test score of 14.66 for the experimental group and 11.31 for the control group. The hypothesis test yielded a sig. (2-tailed) value of 0.001, which was smaller than the α level of 0.05, indicating a significant difference in post-test scores between the experimental and control groups. Based on these findings, it can be concluded that the use of fractional dominoes enhances the mathematical communication skills of second-grade elementary school students.